2014
DOI: 10.1515/hmbci-2013-0067
|View full text |Cite
|
Sign up to set email alerts
|

Energy metabolism and hindbrain AMPK: regulation by estradiol

Abstract: Nerve cell energy status is screened within multiple classically defined hypothalamic and hindbrain components of the energy balance control network, including the hindbrain dorsal vagal complex (DVC). Signals of caudal DVC origin have a physiological role in glucostasis, e.g., maintenance of optimal supply of the critical substrate fuel, glucose, through control of motor functions such as fuel consumption and gluco-counterregulatory hormone secretion. A2 noradrenergic neurons are a likely source of these sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…Current evidence has shown that estradiol controls hypothalamic astrocyte AMPK and hindbrain catecholamine-dependent activation of this cell-specific sensor by hypoglycemia [106] . In keeping with this evidence, recent data have also proposed that 17β-estradiol acting on AMPK in the hindbrain dorsal vagal complex (DVC) might be also involved in the induction of counterregulatory responses [107] . Although these data are of relevance, further work involving genetic models will be necessary to address the physiological relevance of estrogen on AMPK-induced effects on glucose homeostasis.…”
Section: Brain Estrogens Stimulate Energy Expenditurementioning
confidence: 81%
“…Current evidence has shown that estradiol controls hypothalamic astrocyte AMPK and hindbrain catecholamine-dependent activation of this cell-specific sensor by hypoglycemia [106] . In keeping with this evidence, recent data have also proposed that 17β-estradiol acting on AMPK in the hindbrain dorsal vagal complex (DVC) might be also involved in the induction of counterregulatory responses [107] . Although these data are of relevance, further work involving genetic models will be necessary to address the physiological relevance of estrogen on AMPK-induced effects on glucose homeostasis.…”
Section: Brain Estrogens Stimulate Energy Expenditurementioning
confidence: 81%
“…AMP-activated protein kinase (AMPK) is considered to be a major metabolic energy sensor. Decreased cellular energy charge (increased AMP/ATP ratio) activates AMPK and then regulates energy metabolic homeostasis ( Briski et al, 2014 ; Zainal Abidin et al, 2015 ). Pharmacologic inhibition of AMPK was reported to alleviate ischemic damage in an ischemia model ( Li et al, 2007 ).…”
Section: Function On Energy Metabolismmentioning
confidence: 99%
“…Hindbrain catecholaminergic (CA) neurons are critically involved in glucoregulatory functions. Selective immunotoxin lesions, gene silencing, chemogenetic activation, and localized glucoprivation have revealed that activation of these neurons is necessary for elicitation of feeding, corticosterone secretion, and elevation of adrenal medullary secretion in response to glucose deficit ( 7 , 33 , 34 , 59 , 62 ). Additionally, CA NST neurons may be involved in producing the increased gastric motility evoked by glucose deficit ( 29 , 66 , 67 ).…”
Section: Introductionmentioning
confidence: 99%